Uma Abordagem para Classificação de Interações Sociais Dinâmicas a partir de seus Atributos - Silva, Thiago H. P.; Laender, Alberto H. F. (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe); 2018: Anais do VI Symposium on Knowledge Discovery, Mining and LearningDO - 10.5753/kdmile.2018.27385, 2018)
Network analyses provide important information for understanding how a network evolves. In this context, some studies focus on classifying nodes and their relationships based on topological properties and centrality metrics. Instead, we discuss the importance of applying the notion of social capital to the classification process. Here, we propose a new approach to classify nodes and edges in temporal multigraphs based on the persistence of the edges’ attributes. Overall, our results show that the social role of the nodes and the strength of their ties are statistically well-defined when compared with several traditional graph metrics.